German Terminology of Accounting and Auditing: Lexical and Semantic Features - Kiyko, S.; Hladkoskok, L.; Saiko, M. (Linguistische Treffen in Wrocław, 2026)
The paper examines the lexical and semantic features of the German terminology system of accounting and auditing. The research corpus comprises approximately 6,000 terms and terminological combinations extracted from specialized dictionaries and online lexicons. The German terminology of accounting and auditing is characterized as an organized, semantically and structurally coherent system of interrelated technical expressions connected by paradigmatic relationships. The thematic classification made it possible to identify ten groups of terms, the largest of which denote operations, actions, and processes (1,688 units), as well as properties, qualities, characteristics, and states (1,237 units). This highlights the process-oriented nature of the examined field. The analysis of paradigmatic relations revealed the active functioning of hyperonymic and hyponymic links, which ensure the hierarchical organization of the terminological material. Synonymy is represented by two main types – semantic identity and semantic similarity – with syntactic synonymic constructions prevailing. Antonymy is represented by four types: contradictory, complementary, contrary, and converse terms. Although less common, homonymy and paronymy still pose certain challenges for the unambiguous understanding of terms. Both intersectoral and intrasectoral homonyms were distinguished, their emergence being attributed to borrowing, semantic word formation, and the functioning of internationalisms across different terminological systems. Overall, the German terminology system of accounting and auditing is characterized by a high degree of systematization, a hierarchical structure, and diverse paradigmatic relations among terminological units, reflecting the complexity and multifaceted nature of the conceptual framework of this field of knowledge.
Keywords: : German terminology; accounting; auditing; paradigmatic relations